Structural characterization of phosphoethanolamine-modified lipid A from probiotic Escherichia coli strain Nissle 1917. Issue 34 (25th June 2019) - Jo, Sung-Hyun; Park, Han-Gyu; Song, Won-Suk; Kim, Seong-Min; Kim, Eun-Jung; Yang, Yung-Hun; Kim, Jae-Seok; Kim, Byung-Gee; Kim, Yun-Gon
Abstract : The probiotic Escherichia coli strain Nissle 1917 is able to colonize the gut more efficiently through lipid A mediated cationic antimicrobial peptide tolerance. Abstract : Gut microbiota, a complex microbial community inhabiting human or animal intestines recently regarded as an endocrine organ, has a significant impact on human health. Probiotics can modulate gut microbiota and the gut environment by releasing a range of bioactive compounds. Escherichia coli ( E. coli ) strain Nissle 1917 (EcN), a Gram-negative bacterial strain, has been used to treat gastrointestinal (GI) disorders ( i.e., inflammatory bowel disease, diarrhea, ulcerative colitis, and so on). However, endotoxicity of lipopolysaccharide (LPS), a major component of the cell wall of Gram-negative bacteria in the gut, is known to have a strong influence on gut inflammation and maintenance of gut homeostasis. Therefore, characterizing the chemical structure of lipid A which determines the toxicity of LPS is needed to understand nonpathogenic colonization and commensalism properties of EcN in the gut more precisely. In the present study, MALDI multiple-stage mass spectrometry analysis of lipid A extracted from EcN demonstrates that hexaacylated lipid A ( m / z 1919.19) contains a glucosamine disaccharide backbone, a myristate, a laurate, four 3-hydroxylmyristates, two phosphates, and phosphoethanolamine (PEA). PEA modification of lipid A is known to contribute to cationic antimicrobial peptide (CAMP) resistance of Gram-negative bacteria. To confirm the role of PEA in CAMP resistance of EcN, minimum inhibitory concentrations (MICs) of polymyxin B and colistin were determined using a wild-type strain and a mutant strain with deletion of eptA gene encoding PEA transferase. Our results confirmed that MICs of polymyxin B and colistin for the wild-type were twice as high as those for the mutant. These results indicate that EcN can more efficiently colonize the intestine through PEA-mediated tolerance despite the presence of CAMPs in human gut such as human defensins. Thus, EcN can be used to help treat and prevent many GI disorders.